Effect of the feeding pattern on rumen wall morphology of cows and sheep - Resende-Junior, João Chrysostomo de; Alonso, Luciano da Silva; Pereira, Marcos Neves; Magallanes, Maria Gabriela Roca; Duboc, Marcela Vieira; Oliveira, Edmarcos Correia de; Melo, Leandra Queiroz de (Brazilian Journal of Veterinary Research and Animal Science, 2006)
Nutritional manipulation of the rumen wall volatile fatty acid absorption capacity can be a strategy to control ruminal acidosis in dairy cows. Aiming to induce morphological rumen wall variation through diet and to establish efficient papillae morphological markers 2 experiments were performed. In experiment 1, seven rumen-cannulated cows were fed with concentrate 1 or 4 times a day for 19 days followed by fasting for 72 hours. Ruminal papillae were collected on days, 0, 4, 12 and 19 of the treatment period, and 24, 48 and 72 hours after onset of fasting which was able to induce papilar involution. Lower concentrate feeding frequency was associated to insulin increasing over time (P=0,02) and higher (P=0,03) mitotic index (MI), but it did not affect other morphological parameters. In experiment 2, two non-simultaneous trials with 3 rumen-cannulated ovines in each, were conducted and animals were fasted abruptly for 72 hours after feeding. Papillae were collected at the end of the feeding period and at the end of the 72 hour fasting period. MI was higher in the feeding period than the in fasting period (P<0,01), but other morphological parameters were not able to respond to nutritional variation. Among the morphologic markers studied MI seems to be the best variable for evaluation of the rumen epithelium morphologic response to feeding plans. Frequency of concentrate feeding may be used to regulate rumen papillae morphology.